Neodymium coordination polymers with propionate, succinate and mixed succinate–oxalate ligands: Synthesis, structures and spectroscopic characterization. (14th December 2015) - Scales, Nicholas; Zhang, Yingjie; Bhadbhade, Mohan; Karatchevtseva, Inna; Kong, Linggen; Lumpkin, Gregory R.; Li, Feng
Graphical abstract: This paper reports the synthesis, spectroscopic characterization, thermal study and crystal structures of three neodymium coordination polymers with propionate, succinate, and mixed succinate–oxalate ligands. Abstract: Three neodymium (Nd) coordination polymers with propionate, succinate and mixed succinate–oxalate ligands have been synthesized and structurally characterized. Nd2 (C3 H5 O2 )6 (H2 O)3 ·3H2 O (1 ) has a 1D polymeric structure built with both ninefold and ten-fold coordinated neodymium polyhedra linked through μ2 -bridging propionate ligands. Nd2 (C4 H4 O4 )3 (H2 O)2 (2 ) has a 3D polymeric structure constructed with two distinct ninefold coordinated neodymium polyhedra linked through three types of succinate ligands, two in μ4 - and one in μ3 -coordination modes. Nd2 (C4 H4 O4 )2 (C2 O4 )(H2 O)4 ·3H2 O (3 ) is built with two types of ten-fold coordinated neodymium polyhedra linked through μ4 -succinate ligands into 2D undulating layers which are further connected through μ2 -oxalate ligands forming a 3D network with channels. Their vibrational modes and thermal stabilities have been further investigated.